In search for biomarkers and potential drug targets for uterine serous endometrial cancer - Dinoi, Giorgia (J Cancer Res Clin Oncol, 2021)
OBJECTIVE: Serous endometrial cancer (USC) is a challenging malignancy associated with metastasis, recurrence and poor outcome. To identify clinically relevant prognostic biomarkers, we focused on a panel of proteins selected after a comprehensive literature review, for tumour profiling of a homogeneous cohort of USC patients. METHODS: Protein levels and localization were assessed by immunohistochemistry analysis in 36 hysterectomy samples. Tissue sections were stained with the following antibodies: Aurora A, phospho (T288) Aurora A, BRCA1, CHK1, CIP2A, Cyclin B1, Cyclin E, E2F-1, phospho (S364) E2F-1, FBXW7, FOXM1, phospho (S9) GSK3Beta, PLK1, phospho (T210) PLK1, PPP2R1B, p73, RAD51. Each marker was evaluated as a continuously-scaled variable for association with disease progression and death, using Cox proportional hazards models. The sample consisted of 36 patients with USC, half with stage III or IV disease. RESULTS: Results showed that higher CHK1 (Checkpoint kinase 1) expression was associated with a decreased risk of progression and death, after adjusting for stage. Interestingly, analysis of a TCGA data set of 109 USC patients corroborates our results showing a favourable prognostic role of CHEK1 after adjusting for stage. Higher FBXW7 (F-box and WD repeat domain containing 7) expression and higher cytoplasmic expression of PPP2R1B (Protein Phosphatase 2 A, Scaffold Subunit Abeta) were each associated with a decreased risk of progression, after adjusting for stage. CONCLUSIONS: In conclusion, results from the present study identify new clinically relevant biomarkers and potential drug targets for uterine serous endometrial cancer. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00432-021-03566-x.